Exploring Learning and Unlearning (II): Effective Study Methods for the Individual Practice of Professional Singers - Cristina RADU (Studia Universitatis Babeş-Bolyai. Musica, 2025)
Education today no longer means just memorizing information and mastering technical procedures. Education today means exploring and discovering as many things as possible from diverse fields that can shed new light on your own field of interest. Education is more creative today, and is now accessible worldwide, just a click away. But discernment in choosing the valuable paths and what we do with the extensive information we acquire; the power to create a coherent structure, the adaptability and the energy to combine training with a broad vision – these are skills that will make the difference in education. The future belongs to those who will never stop learning[1] - this modern mindset is like a motto for my articles on learning and unlearning. This article attempts to outline why individual study is a necessity for singers as it has always been but must be structured by a clear methodology in which each participant is also a co-author. Because each artist presents his uniqueness – benefiting from anatomical-physiological and psychological particularities – the study methods are permanently adapted to everyone. A good teacher knows and practices these permanent adjustments of his pedagogical manner to effectively respond to the needs of each young singer in training. But the singer in his individual practice also needs to become aware of the benefits of a progressive adaptation and particularization of his personal training. And to periodically review the correctness of his vocal technique, of his artistic perspective, using tools such as unlearning and re-learning. This mental flexibility, combined with an analytical and conscious study – can lead to a more efficient education and good training for young singers. The structure of the article includes topics such as: Effective study methods for professional singers; Singer’s individual practice in approaching a new musical score; Unlearning Tasks; Creativity in vocal training; Time Management for Singers.